2011
DOI: 10.1177/0192623310397557
|View full text |Cite
|
Sign up to set email alerts
|

Recommended Neuroanatomical Sampling Practices for Comprehensive Brain Evaluation in Nonclinical Safety Studies

Abstract: Adequate tissue sampling is known to reduce the likelihood that the toxicity of novel biomolecules, chemicals, and drugs might go undetected. Each organ, and often specific structurally and functionally distinct regions within it, must be assessed to detect potential site-specific toxicity. Adequate sampling of the brain requires particular consideration because of the many major substructures and more than 600 subpopulations of generally irreplaceable cells with unique functions and vulnerabilities. All known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…This is extremely important in order to minimize false negative findings (Switzer et al, 2011). Most neurotoxicants that produce neuronal destruction as typified by cells with pycnotic nuclei generally have their maximal effects 3-5 days after exposure (for some neurotoxicants this time may vary greatly).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is extremely important in order to minimize false negative findings (Switzer et al, 2011). Most neurotoxicants that produce neuronal destruction as typified by cells with pycnotic nuclei generally have their maximal effects 3-5 days after exposure (for some neurotoxicants this time may vary greatly).…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, there should be tissue sections taken from all major regions of the central nervous system (CNS). Even then, it has been estimated by Switzer et al (2011) that it would take about 64 sections to have a fair probability of detecting neurotoxicity were it produced by a new compound. Sections used for FDA submissions are generally obtained from the brain after immersion fixation rather than perfusion fixation and are typically stained with hematoxylin and eosin (H&E).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a recent discourse on comprehensive brain sampling (Switzer, Lowry-Franssen, and Benkovic 2011) reported that small structural lesions elicited by half of the 14 known chemical and pharmaceutical neurotoxicants reviewed might not (N ¼ 3; domoic acid, kainic acid, and methamphetamine) or would not (N ¼ 4; alcohol, carbonyl sulfide, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine [MPTP], and 2-amino-MPTP) be detected by conventional 3-level sampling of rodent brain. In this treatise, the suggested strategy for sampling adult rodent brains to ensure that all 600þ unique populations of neural cells always will be subject to microscopic evaluation is to produce coronal step sections throughout the entire organ at an interval of 0.32 mm (yielding 60-65 sections per rodent) in at least one toxicity study for each novel xenobiotic (Switzer, Lowry-Franssen, and Benkovic 2011). This exhaustive approach might have merit for certain situations in which a comprehensive neuroanatomic analysis is the main point of a neurotoxicity-oriented investigation (Tier II).…”
Section: Introductionmentioning
confidence: 95%
“…The routine practice at many institutions for rodent brain sampling evaluates three or four brain levels (typically rostral forebrain [cerebral cortex and basal nuclei], caudal forebrain [cerebral cortex and hippocampus with either diencephalon or rostral midbrain], and hindbrain [usually cerebellum with pons and/ or cerebellum with medulla oblongata]; Morawietz et al 2004). In contrast, a recent discourse on comprehensive brain sampling (Switzer, Lowry-Franssen, and Benkovic 2011) reported that small structural lesions elicited by half of the 14 known chemical and pharmaceutical neurotoxicants reviewed might not (N ¼ 3; domoic acid, kainic acid, and methamphetamine) or would not (N ¼ 4; alcohol, carbonyl sulfide, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine [MPTP], and 2-amino-MPTP) be detected by conventional 3-level sampling of rodent brain. In this treatise, the suggested strategy for sampling adult rodent brains to ensure that all 600þ unique populations of neural cells always will be subject to microscopic evaluation is to produce coronal step sections throughout the entire organ at an interval of 0.32 mm (yielding 60-65 sections per rodent) in at least one toxicity study for each novel xenobiotic (Switzer, Lowry-Franssen, and Benkovic 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Basic considerations include the study purpose (eg, general screen vs dedicated neurotoxicity analysis), processing conditions (eg, tissue fixation by immersion for general toxicity studies vs perfusion for dedicated neurotoxicity studies), embedding medium (eg, paraffin vs plastic), and nervous system sampling strategy. [12][13][14][15][16][17] In some instances, these details reflect the preferences of the sponsoring institution and/or the scientific team. In other cases, study parameters are dictated by regulatory guidelines.…”
mentioning
confidence: 99%